When the brain simulates stopping: neural activity recorded during real and imagined stop-signal tasks (2020)
It has been suggested that mental rehearsal activates brain areas similar to those activated by real performance. Although inhibition is a key function of human behavior, there are no previous reports of brain activity during imagined response cancellation. We analyzed event-related potentials (ERPs) and time-frequency data associated with motor execution and inhibition during real and imagined performance of a stop-signal task. The ERPs characteristic of stop trials-that is, the stop-N2 and stop-P3-were also observed during covert performance of the task. Imagined stop (IS) trials yielded smaller stop-N2 amplitudes than did successful stop (SS) and unsuccessful stop (US) trials, but midfrontal theta power similar to that in SS trials. The stop-P3 amplitude for IS was intermediate between those observed for SS and US. The results may be explained by the absence of error-processing and correction processes during imagined performance. For go trials, real execution was associated with higher mu and beta desynchronization over motor areas, which confirms previous reports of lower motor activation during imagined execution and also with larger P3b amplitudes, probably indicating increased top-down attention to the real task. The similar patterns of activity observed for imagined and real performance suggest that imagination tasks may be useful for training inhibitory processes. Nevertheless, brain activation was generally weaker during mental rehearsal, probably as a result of the reduced engagement of top-down mechanisms and limited error processing.